2010
DOI: 10.1111/j.1745-9125.2010.00194.x
|View full text |Cite
|
Sign up to set email alerts
|

Poverty, Infant Mortality, and Homicide Rates in Cross‐national Perspective: Assessments of Criterion and Construct Validity*

Abstract: This paper assesses the extent to which the infant mortality rate might be treated as a “proxy” for poverty in research on cross-national variation in homicide rates. We have assembled a pooled, cross-sectional time-series dataset for 16 advanced nations over the 1993–2000 period that includes standard measures of infant mortality and homicide and also contains information on two commonly used “income-based” poverty measures: a measure intended to reflect “absolute” deprivation and a measure intended to reflec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(45 citation statements)
references
References 41 publications
(92 reference statements)
0
44
0
1
Order By: Relevance
“…In addition, economic inequality and ethnic heterogeneity exert a positive influence on homicide separately as expected (Altheimer, 2008;Chon, 2011;Fearon, 2011;He et al, 2003;Maume & Lee, 2003;Messner, 1982;Messner, Raffalovich, & Sutton, 2010;Nivette, 2011;Ouimet, 2012;Pratt & Cullen, 2005). Inequality, both absolute and relative, makes it difficult to maintain any spirit of e pluribus unum.…”
Section: Discussionmentioning
confidence: 88%
“…In addition, economic inequality and ethnic heterogeneity exert a positive influence on homicide separately as expected (Altheimer, 2008;Chon, 2011;Fearon, 2011;He et al, 2003;Maume & Lee, 2003;Messner, 1982;Messner, Raffalovich, & Sutton, 2010;Nivette, 2011;Ouimet, 2012;Pratt & Cullen, 2005). Inequality, both absolute and relative, makes it difficult to maintain any spirit of e pluribus unum.…”
Section: Discussionmentioning
confidence: 88%
“…Messner, Raffalovich, and Sutton () challenged Pridemore's interpretation of the meaning of infant mortality based on their analyses of 16 developed countries. They found that infant mortality rate was more strongly related to a measure of relative poverty (those who earn 60 per cent of the national median income) than a measure of absolute poverty (the percentage who can only afford a basic level of subsistence) (r = 0.744 vs. r = 0.539).…”
Section: Research On Inequality and Homicidementioning
confidence: 99%
“…Cross-national studies of homicide (the crime most comparably measured across countries) usually find null (e.g., Barber 2006; Messner et al 2010; 2011) or even perplexingly negative effects (e.g., Antonaccio and Tittle 2007; Barber 2000, 2009; Messner et al 2002) of the male-to-female sex ratio. In a meta-analysis of studies in this genre, Nivette (2011) found that the population sex ratio falls among the weakest and least-consistent predictors of national homicide rates (see also Pratt and Cullen 2005).…”
Section: Prior Researchmentioning
confidence: 99%